Comparison of the efficacy of Oxford unicondylar replacement for the treatment of spontaneous osteonecrosis of the knee versus medial knee osteoarthritis: a meta-analysis - Pengyu Liu; Liangliang Li; Jiaju Yang; Hao Li; Yuhua Feng; Zhipeng Qin; Min Zhang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective Meta-analysis of the comparative efficacy of Oxford unicompartmental knee arthroplasty (OUKA) for the treatment of spontaneous osteonecrosis of the knee (SONK) and medial knee osteoarthritis (MKOA). Methods A computerized search was conducted for literature related to OUKA treatments of SONK and MKOA across various databases, including the China National Knowledge Infrastructure, WAN FANG, VIP, SinoMed, Cochrane Library, PubMed, Embase, and Web of Science, covering the period from each database's inception to September 2023. Literature screening, quality assessment and data extraction were performed according to the inclusion and exclusion criteria. After extracting the literature data, RevMan 5.4 software was applied to analyse the postoperative knee function score, postoperative knee mobility, postoperative pain, bearing dislocation rate, aseptic loosening, postoperative progression of posterolateral arthritis, and revision rate. Result A total of 9 studies were included, including 6 cohort studies and 3 matched case‒control studies. A total of 1544 knees were included, including 183 in the SONK group and 1361 in the MKOA group. The meta-analysis results showed that the SONK and MKOA groups showed a significant difference in postoperative knee function scores [MD = 0.16, 95% CI (− 1.20, 1.51), P = 0.82], postoperative knee mobility [MD = − 0.05, 95% CI (− 1.99. 1.89), P = 0.96], postoperative pain [OR = 0.89, 95% CI (0.23, 3.45), P = 0.87], rate of bearing dislocation [OR = 1.28, 95% CI (0.34, 4.81), P = 0.71], aseptic loosening [OR = 2.22, 95% CI (0.56, 8.82), P = 0.26], postoperative posterolateral arthritis progression [OR = 2.14, 95% CI (0.47, 9.86), P = 0.33], and revision rate [OR = 1.28, 95% CI (0.53, 3.04), P = 0.58] were not statistically significant. Conclusion OUKA treatment with SONK and MKOA can achieve similar satisfactory clinical results.